Penerapan Penggunaan Pupuk Organik untuk Tanaman Padi Berkelanjutan di Kecamatan Meureubo, Kabupaten Aceh Barat - Agustiar Agustiar; Sufriadi Sufriadi; Aswin Nasution (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Farmers Developing Their Potential to Increase Agricultural Production Self-development for farmers must be achieved by shifting focus toward the use of organic fertilizers, supporting sustainable agriculture. The use of organic fertilizers is highly recommended to stimulate economic growth within farming communities in specific areas. Enhanced production and productivity serve as key indicators in achieving maximum yields, aiming for optimal farm income and profitability in agriculture. Increased production aligns with the balanced application of liquid fertilizers in rice cultivation. Farmers are expected to contribute positively to the sustainability of agriculture by applying liquid fertilizers to foster eco-farming and sustainable agricultural practices.